Intermediating climate change: conclusions and new research directions - Tosun, Jale; Tobin, Paul; Farstad, Fay (Policy studies, 2023)
The urgency and threats of climate change have elevated the issue to a prominent - albeit often contested - position within the policy process. Resultantly, climate politics and climate change governance have received enhanced attention in both the academic literature and in real-life discourse. Yet, except regarding certain empirical contexts, there has been a lack of conceptualization or analysis of intermediating actors in climate politics - what we term “climate intermediaries” - that bridge between different types of actors and different levels of governance. This Special Issue sought to reduce this research gap by analyzing the strategies, interactions, and impacts in the policy process of these “go-betweens”, across three continents. In this concluding article, we take stock of the insights provided by the individual contributions and offer answers to the three research questions that guided the Special Issue. In addition, we provide some suggestions for future research avenues and concluding reflections.
Gesehen am 29.07.2024